THE EFFECT OF BURNOUT SYNDROME ON TURNOVER INTENTION USING ORGANIZATIONAL COMMITMENT AS AN INTERMEDIATE VARIABLE - Maya Weka Santi; Nurhasmadiar Nandini; Gamasiano Alfiansyah (Indonesian Journal of Health Administration, 2020)
Background: The average of employee turnover rate in Surabaya Surgical Hospital was quite high roughly about 16.21% in 2011 until 2015. Employees’ negative behavior or feelings due to long exposure to an emotional stressor are called burnout syndrome which could trigger turnover in an organization.Aims: This study analyzed the effect of burnout syndrome towards turnover intention using organizational commitment as an intermediate variable.Methods: This study was cross-sectional research by involving 126 respondents as samples according to the proportion of each unit at Surabaya Surgical Hospital. Data were analysed statistically using multiple linier regression.Results: Respondents were mostly female (65.1%) and in the age group of 26-35 years (62.7%). Most of them were early adults, permanent employees (95.2%), and undergraduates (89.7%). While the minority have worked for 3 up to 4 years (40.5%). Burnout syndrome had a significant effect on employees’ organizational commitment. Organizational commitment showed a significant effect on turnover intention, while burnout syndrome did not show a significant effect on turnover intention.Conclusion: Burnout syndrome did not directly affect turnover intention but became a possible cause of turnover intention through organizational commitment as the intermediate variable. The results of this study could be the basis for hospital managers to decrease employee’s turnover intention by minimizing burnout syndrome and increasing organizational commitment with a better reward system. Keywords: burnout syndrome, organizational commitment, turnover intention, hospital.